Վանականների ուխտադրութեան ծէսերի վաղեմութեան եւ հայկական տարբերակի շուրջ - Ծատուրեան, Անանիա աբղյ. (Մայր Աթոռոյ Սրբոյ Էջմիածնի)
Наряду с распространением отшельничества, монашества и развитием монашеских орденов в Церкви сформировалась церемония принятия монахами обета. Сохранились два обряда монашеских обетов: чин «Малой рясы» и «Большой рясы». Самое раннее описание этих обрядов содержится в книге «О церковной иерархии», приписываемой Псевдо-Дионисию Ареопагиту. Армянский список обрядов под названием «Орhнутунабер цуцак» («Список благословений») является одним из важных свидетельств, подтверждающих давность монашеского ритуала принятия обетов, и после рукописи Барберини, содержащей греческий обряд, две самые ранние копии армянского требника Маштоц – рукопись №457 Конгрегации мхитаристов Венеции (X век) и рукопись №1001 Матенадаран Месропа Маштоца (X век) — одни из старейших. Армянская версия этих чинов, вероятно, была переведена в V веке, когда по приказу католикоса св. Саака I Партева был составлен «Орhнутунабер цуцак» (408—439). Переводчиком, возможно, был св. Моисея Хоренского. Along with the spread of hermitry, monasticism and the development of monastic orders, the ceremony of the monks’ making a vow was shaped in the Church. Two rites of monastic vows have been preserved: the canons of “Small cassock” and “Big cassock”. The earliest description of these rites is available in the book “The Ecclesiastical Hierarchy” attributed to Pseudo-Dionysius the Areopagite. The Armenian “Orhnutunaber” is one of the important evidences proving the agedness of the monastic ritual of making vows, and after the Barberini manuscript containing the Greek rite, the two earliest copies of the Armenian Mashtots ritual book – manuscript No. 457 of the Mekhitarist Congregation of Venice (10th century) and manuscript No. 1001 of Mesrop Mashtots Matenadaran (10th century) — are among the oldest ones. The Armenian version of these canons was probably translated in the 5th century, when by the order of Catholicos St. Sahak the Parthian “Orhnutunaber” was compiled (408—439). The translator was perhaps Movses of Khoren.
Keywords: Կրօնագիտութիւն